RIDDAHDAN KEBEBASAN BERAGAMA DALAM ALQURAN - Dede Rodin (AHKAM : Jurnal Ilmu Syariah, 2014)
Apostasy and Religious Freedom in the Alquran. The concept of apostasy should be understood in the context of religious freedom which is a basic principle of every person under Islam. Thus, the apostate merely moves religions without participating in provocative acts against Islam and Muslims, and not having imposed sanctions in this world but in the hereafter as affirmed within the verses in the Alquran. Now, it so happens that sanctions of murder mentioned by the prophet -if hadis is viewed validly- apply to the apostate who participated in provocation and hostility contrary to the administration of Islam and Muslims. This penalty is also just able to be enforced at a new practical level, if the legal provisions have become positive law which has been made into legislation or regulation by a country, so that the law is binding and applies to all the citizens.DOI: 10.15408/ajis.v14i2.1284